679 High fiber diet modifies gut microbiome, propionate production, intratumor immune response and is associated with outcome in patients with lung cancer treated with immune checkpoint inhibitors. (9th November 2020) - Richard, Corentin; Benlaifaoui, Myriam; Ouarzadi, Omar El; Diop, Khoudia; Desilets, Antoine; Malo, Julie; Belkaid, Wiam; Leblanc, Andréanne; Lamontagne, Julien; Messaoudene, Meriem; Elkrief, Arielle; Routy, Bertrand
Abstract : Background: The gut microbiome plays a key role in immune checkpoint inhibitors (ICI) efficacy and several strategies are currently being investigated to improve microbiome composition. The impact of a specific diet on microbiome modulation and clinical outcomes remains unknown. In this study, we assessed the effects of a high fiber diet on clinical outcomes as well as on microbiome composition, production of fecal metabolites, and intratumor immune infiltration in metastatic non-small cell lung cancer (mNSCLC) patients amenable to ICI. Methods: In this prospective study, 39 chemotherapy-refractory or naive patients with mNSCLC treated with ICI alone or in combination with chemotherapy completed a validated dietary survey. Based on the total fiber intake, patients were divided into high vs low fiber groups (HF vs LF). Objective response rate (ORR), progression-free survival (PFS) and overall survival (OS) were compared between both groups. In addition, fecal and tumor samples were collected prior to ICI initiation. Fecal metagenomic sequencing was performed and fecal short-chain fatty acids (SCFA) were measured by LC-MS/MS. Tumoral transcriptome profiling was performed through RNA sequencing to define differentially expressed pathways. Results: Baseline characteristics were well balanced between both groups, including body mass index (BMI) and PD-L1 status. Median PFS for the HF group was longer compared to the LF group (27.4 vs 12.6 months). Microbiome metagenomic profiling revealed higher baseline alpha diversity (p=0.048) in the HF group compared to the LF group. Bifidobacterium, Alistipes, and Bacteroides salyersiae were enriched in the HF group while Fusobacterium was overrepresented in the LF group. SCFA measurement revealed that a high level of propionate correlated with a significantly longer OS (not reached vs 18.4. months, p=0.02) in the entire cohort. Moreover, propionate levels were significantly higher in the HF vs LF group (p=0.02). At the tumor level, RNA sequencing demonstrated a downregulation of DNA repair mechanisms and an upregulation of humoral and adaptive immune responses in the HF group. Conclusions: In this study, we demonstrated that a HF diet in patients with mNSCLC was associated with better clinical outcomes. Importantly, HF was associated with an enrichment of previously reported beneficial gut bacteria. Moreover, propionate correlated with longer OS and was increased in the HF group. This study provides further insights into how the diet can beneficially shift the microbiome composition and intratumor immune responses in patients with mNSCLC treated with ICI and this may lead to novel, dietary-geared therapeutic avenues in the oncomicrobiome arena. Ethics Approval: The study was approved by CRCHUM Institution, s Ethics Board, approval number 17.035.